Feeding ecology of piscivorous brown trout (Salmo trutta L.) in a subarctic watercourse - Jensen, Hallvard; Bøhn, Thomas; Amundsen, Per-Arne; Aspholm, Paul Erik (Finnish Zoological and Botanical Publishing Board, 2004)
Source at http://www.sekj.org/AnnZool.html . Feeding ecology of piscivorous brown trout was studied in the Pasvik watercourse, Norway and Russia. The watercourse is heavily regulated for hydroelectric purposes, and 5000 brown trout > 25 cm are stocked annually to compensate the negative impacts of the impoundments. Stocked and wild trout had almost identical diets consisting mainly of vendace Coregonus albula and partly of whitefish Coregonus lavaretus. Vendace has recently invaded the watercourse, and totally dominated the brown trout diet in the upstream part, where it has become the dominant species in the pelagic habitat. In the downstream part, where vendace were less prevalent, whitefish contributed to a larger extent to the trout diet. No correlation between predator (brown trout) and prey (vendace) lengths was found in the upstream part, and only a weak positive correlation was found in the downstream part. The length of whitefish eaten by brown trout, in contrast, showed a positive correlation with predator length in both the upstream and downstream part. The prey selection of brown trout was, to a large extent, explained by the differences in density and size-structure of coregonids in the two sampling areas.